2018
DOI: 10.1111/jdv.15051
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune bullous diseases in non‐HIVKaposi's sarcoma: a retrospective study in a large cohort of patients

Abstract: Bullous diseases seem to be more frequent among patients with KS, supporting the hypothesis that HHV-8 may be involved in their pathogenesis. Therapeutic management of these cases should take into account KS-inducing potential of corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…The iatrogenic subtype of KS was originally described in patients who had undergone organ transplantation, in particular kidney transplants followed by high-dose immunosuppressants [9]. Since then, several other cases have been reported in patients who have not had organ transplantation yet have been receiving immunosuppressants, including systemic and topical corticosteroids, for a variety of disorders (blood diseases, kidney diseases, atopic dermatitis, asthma, chronic inflammatory disease [8,[10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The iatrogenic subtype of KS was originally described in patients who had undergone organ transplantation, in particular kidney transplants followed by high-dose immunosuppressants [9]. Since then, several other cases have been reported in patients who have not had organ transplantation yet have been receiving immunosuppressants, including systemic and topical corticosteroids, for a variety of disorders (blood diseases, kidney diseases, atopic dermatitis, asthma, chronic inflammatory disease [8,[10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…24 Half of these 14 patients developed KS after the onset of bullous disease, whereas the other half developed a bullous disease after being diagnosed with KS. 24 Only a few cases on concurrent HHV-8 and BP have been reported in the literature. 12,21,22 HHV-8 identification in KS with BP has been reported only in one patient in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent retrospective study in non-HIV KS patients reported that 14 (1.03%) of 1362 patients with classic or iatrogenic KS also suffered from bullous disease. 24 Half of these 14 patients developed KS after the onset of bullous disease, whereas the other half developed a bullous disease after being diagnosed with KS. 24 Only a few cases on concurrent HHV-8 and BP have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly pertinent given the increased incidence of autoimmune bullous diseases in patients with noneHIV-associated KS. 6 As immunotherapies are being increasingly developed, we must find ways to leverage therapeutic benefits in rare diseases such as KS. Further trials are warranted to explore checkpoint inhibition in KS, especially whether cytotoxic T-lymphocyteeassociated protein 4 inhibition enhances programmed cell death protein 1 inhibition to lead to further cytotoxic T-cell destruction of KS-infected cells.…”
Section: Discussionmentioning
confidence: 99%